Robust Stability of Sliding Mode Control for Pitch Attitude Boeing 747 Aircraft System - Setiawan, Paulus; Matuan, Lorenso Oldiardo; Astuti, Yenni; Sudibya, Bambang; Dermawan, Denny; Kurniawan, Freddy; Lasmadi, Lasmadi (Institut Teknologi Dirgantara Adisutjipto, 2025)
Modern aircraft have experienced rapid development at this time, which is proven by the discovery of more complex systems on aircraft. One of the systems that has experienced rapid development is the autopilot, which can control the aircraft automatically. The design of the pitch attitude system begins by collecting data on the longitudinal motion of the aircraft, which is then converted into a mathematical equation of the transfer function for the pitch motion. After the pitch attitude instability is identified, a compensator is made to improve the stability of the pitch motion, with the compensator used in this study being the lead compensator. The main objective of this study is to create a system that can identify parameter values on the Luenberger Observer control and sliding mode control (SMC) in the flight control system. The results of several test experiments clearly show that the proposed SMC controller can produce better and more stable system performance.